2013
DOI: 10.3382/ps.2012-02734
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the gastrointestinal ecology in alternatively raised poultry and the potential for molecular and metabolomic assessment

Abstract: Consumer demand for nonconventional poultry products continues to increase in the United States. In pasture flock and organic poultry production, probiotics and prebiotic feed additives have potential advantages because they are thought to promote intestinal health and may offer a replacement for current intervention strategies that are not considered acceptable for these production systems. Prebiotics have been demonstrated to produce effects on the gastrointestinal tract including modulation of microflora by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 169 publications
0
29
0
1
Order By: Relevance
“…These approaches offer an opportunity to comprehensively analyze uncultured and rare microbial communities from various environmental samples and can be also applied to improve poultry production and enhance food safety (Diaz-Sanchez et al, 2013;Park et al, 2013). To date, in the field of poultry science, only a few studies have been performed to investigate microbial communities by using high-throughput sequencing (Callaway et al, 2009;Singh et al, 2012;Yin et al, 2013).…”
Section: Spatial Heterogeneity and Stability Revealed By Shared Otu Amentioning
confidence: 99%
“…These approaches offer an opportunity to comprehensively analyze uncultured and rare microbial communities from various environmental samples and can be also applied to improve poultry production and enhance food safety (Diaz-Sanchez et al, 2013;Park et al, 2013). To date, in the field of poultry science, only a few studies have been performed to investigate microbial communities by using high-throughput sequencing (Callaway et al, 2009;Singh et al, 2012;Yin et al, 2013).…”
Section: Spatial Heterogeneity and Stability Revealed By Shared Otu Amentioning
confidence: 99%
“…Continued advances in a variety of genetic functional screening techniques coupled with high throughput sequencing approaches have now made it possible to contemplate a much more comprehensive resolution to understanding the complex nature of biological systems such as Salmonella-host relationships [272,[275][276][277][278]. These approaches should help uncover some of the more subtle nuances in pathogenesis mechanisms and in turn achieve a better understanding of how Salmonella interacts with its poultry host [278,279]. The following sections will discuss these developments in general terms and how they might be used for understanding foodborne Salmonella functionality and subsequent application in vaccine development.…”
Section: Advances In Biologymentioning
confidence: 99%
“…Broiler chicken meat comprises the majority of the poultry meat industry, and ensuring the health and productivity of broilers has become a key aspect of this industry (Ballou et al., ). Recent studies using high throughput sequencing, have shown the role of the gastrointestinal tract (GIT) microbiome in gastrointestinal development, nutrient absorption, and pathogen invasion resistance (Crhanova et al., ; Pan & Yu, ; Park et al., ; Pedroso & Lee, ; Yeoman et al., ). Concurrently, initiatives to control antibiotic use in production animals, especially the restriction in use of growth promoters worldwide to prevent the emergence of antibiotic resistance has made the manipulation of intestinal microbiomes in poultry an attractive alternative to support innate immunity and improve health (Kogut & Arsenault, ; Pedroso & Lee, ), as well as productivity (Singh et al., ).…”
Section: Introductionmentioning
confidence: 99%